Behavioral tuning of spider silk thread stiffness circumvents biomaterial trade-offs - Jonas O. Wolff; Daniela C. Rößler; Anna-Christin Joel; Vincent Jackel; Sebastian Büsse; Peter Michalik; Martín J. Ramírez (Proceedings of the National Academy of Sciences, 2026)
Biological polymers often face a trade-off between stiffness, strength, and extensibility: Materials that are strong and stiff tend to be brittle, while those that are elastic and extensible usually lack strength. Here, we show that netcasting spiders (Deinopidae) overcome this trade-off by forming mixed-silk metastructures, which enable both high elastic deformation and load resistance. These spiders have evolved a unique predatory strategy, casting a sticky silk web over prey, which subjects the web radii to extreme strains far exceeding those sustained by typical spider silk fibers. The radii consist of a compound filament with an elastomeric core surrounded by looped bundles of thin fibers. This architecture results in an unusual mechanical profile: The threads are initially compliant and highly extensible, but they stiffen as the fiber loops straighten, enhancing load-bearing capacity. Notably, spiders control this compound architecture through a reel-spinning technique, controlling loop formation and fiber mixture to establish an elasticity gradient across the web—stiff and strong in the main frame lines, yet soft and hyperelastic in the lower radii that undergo the greatest deformation during prey capture. These findings represent a unique case of behavioral modulation of silk processing to circumvent biomaterial trade-offs, enabling extraordinary dynamics and specialization of web architecture. The herein described principle of looped fiber-reinforced elastomers may also be transferred to the design of artificial materials for applications that require both high elasticity and strength.